A novel oral endoscopic biopsy procedure to obtain rumen epithelial samples - Ramos Zayas, Yareellys; Cantú Reyes, Saúl Adrián; Tristán Casas, Iris I.; Kawas Garza, Jorge R. (Multidisciplinary Digital Publishing Institute, 2022)
Most in vivo studies related to ruminal development in calves use invasive techniques involving rumen-fistulated or euthanized animals. In consideration of animal welfare, we developed an oral endoscopic biopsy procedure to allow the obtaining of rumen epithelial samples, thus serving as an alternative for measuring the height and width of rumen papillae in calves in a safe, quick, and efficient manner that allows the slaughtering of calves to be avoided. This procedure was tested on 12 Brangus crossbred calves randomly distributed in two groups, with one fed a meal starter and the other an extruded starter feed. Calves underwent a 12-h fasting period, were restrained in a squeeze chute, administered a dose of atropine, and sedated with xylazine before the oral endoscopic biopsy procedure. A 120 cm long Olympus® oral flexible video endoscope and forceps were used to collect cranial–dorsal sac rumen epithelial tissue samples of approximately 0.5 mm. Endoscopy was successful in all 12 calves and the collected tissue samples were placed in formalin (10%) for further processing for obtaining rumen papillae measurements. Consumption of the extruded starter feed resulted in the increased (p = 0.035) width of rumen papillae. The oral endoscopic biopsy procedure implemented in this study was demonstrated to be successful and is thus an alternative technique for studying rumen epithelial development and morphometric alterations in calf rumen tissue.